Wyznaczanie Współczynników Transportu w Gazach za Pomocą Rur Uderzeniowych - A.S. Cukrowski; J. Luboński; Z.A. Walenta (Engineering Transactions)
Possibilities of the application of a shock tube for the determination of transport coefficients in gases arc presented. At the beginning, a description of phenomena occurring in the shock tubes (Section 2), as well as a thermodynamic description of the viscosity and thermal conductivity coefficients (Section 3) are given. In Section 4.1 it is shown that these coefficients cannot be obtained from the phenomenological fluid dynamic description of the shock wave structure. The molecular description of this structure allows to determine the intermolecular potentials and to calculate the transport coefficients (Section 4.2). Examination of the viscous boundary layer behind the primary shock wave (Section 4.3) and the thermal boundary layer behind the reflected shock wave (Section 4.4) enables us to determine the dependence of transport coefficients on the temperature. The majority of results are obtained from the reflected shock wave examination. In the table there are indicated the individua1 authors, kinds of gases, temperature ranges, experimental techniques, and the corresponding theoretical approaches.